Multitarget linear-quadratic control problem: Semi-infinite interval - L. Faybusovich (2018)
We consider multitarget linear-quadratic control problem on semi-infinite interval. We show that the problem can be reduced to a simple convex optimization problem on the simplex. Copyright © 2012 L. Faybusovich and T. Mouktonglang.